Scientometric Analysis of Iranian Scientific Productions in the Field of Ophthalmology - Leila Rezaei (Journal of Clinical and Basic Research, 2018)
Background and objectives: Evaluation of scientific productions in different fields using scientometric methods is indispensable for determining scientific trends. The purpose of this study was to perform a scientometric evaluation of Iran’s scientific productions in the field of ophthalmology. Methods: We investigated all scientific papers in the field of ophthalmology that have been indexed in the Web of Science from 2000 to the end of 2018. The VOSviewer software (version 1.6.9) was used to draw bibliometric maps considering a threshold of 20 times for the keywords used in this field of medicine. Results: Iran ranked 19th in the world in terms of scientific production on ophthalmology. H-Index of documents written by Iranian authors was 38, with an average citation per item of 7.13. Overall, the documents had received 7262 citations, 6.2% of which were self-citation. We observed that the rate of scientific production has grown dramatically since 2014. Tehran University of Medical Sciences (37.19%) was the most prolific organization in Iran and Seyyed Hassan Ghazizadeh Hashemi (8.63%) was the most prolific Iranian author in this field. All keywords retrieved from the documents on ophthalmology were analyzed, and an ophthalmologist separated the keywords into five clusters. The most frequently used keywords in ophthalmology-related papers belonged to the clusters of Treatment of Retinal Diseases and Glaucoma with 49 appearances. Conclusion: Our results show that the growth of scientific productions in the field of ophthalmology in Iran and its contribution to the global science production is favorable. However, Iranian authors are recommended to pay more attention to selection of appropriate journals for publishing their scientific papers since publishing in prestigious journals with a high impact factor subsequently increases visibility and citation rates.